2014
DOI: 10.1016/j.eats.2014.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction Internal Fixation of Distal Clavicle Fracture With Supplementary Button Coracoclavicular Fixation

Abstract: Distal clavicle fractures are common, and no standard treatment exists. Many different surgical modalities exist. This report describes an open reduction internal fixation technique that achieves both plate and coracoclavicular stabilization using a button device. A precontoured superior-lateral plate is secured to the clavicle. A 3.2-mm spade-tipped drill bit is drilled across the clavicle and coracoid, passing through 4 cortices. The button is loaded onto an insertion device, passed across the 4 cortices, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Unstable or severely displaced lateral clavicle fractures need to be treated operatively. Numerous surgical techniques have been described in the literature [17][18][19][20]. In this context, hook plating was routinely used for this entity, leading to controverse results with respect to irritation of the skin in contrast to good to excellent functional outcome [9,20].…”
Section: Discussionmentioning
confidence: 99%
“…Unstable or severely displaced lateral clavicle fractures need to be treated operatively. Numerous surgical techniques have been described in the literature [17][18][19][20]. In this context, hook plating was routinely used for this entity, leading to controverse results with respect to irritation of the skin in contrast to good to excellent functional outcome [9,20].…”
Section: Discussionmentioning
confidence: 99%
“…El uso de la artroscopia, además de ser una técnica mínimamente invasiva que respeta los tejidos y nos posibilita acceder a la base de la coracoides con una mínima disección, nos permite además realizar un diagnóstico y tratamiento de la patología articular glenohumeral o del manguito de los rotadores en caso de que existiera. (Burkhart habla de hasta el 40% de los casos en luxaciones acromioclaviculares) [16][17][18][19][20][21][22] .…”
Section: Discussionunclassified
“…1 Few authors have combined the biomechanical advantages of fracture-site fixation plus CC fixation, and they have reported good clinical and radiologic outcomes. 16,17 Shin et al 4 have reported successful union rates after performing interfragmentary fixation using 2 nonabsorbable suture tension bands in a figureof-8 configuration plus CC fixation using 2 suture anchors. They argued that the posteromedial suture anchor in position of the torn conoid ligament plays an important role by restraining the medial clavicle from vertical displacement.…”
Section: Discussionmentioning
confidence: 99%